1999
DOI: 10.1007/s004210050503
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill running starting 3 months after orchidectomy restores femoral bone mass in rats

Abstract: The present study was designed to provide data on the effects on femoral bone of endurance training starting only 3 months after orchidectomy in rats. A total of 70 Wistar male rats were used at 8 weeks of age. On day 0 of the experiment, 10 rats were killed by cervical dislocation to be used as first controls. Among the 60 other animals, half was surgically castrated (CX) or sham operated (SH). On day 90, 10 CX and 10 SH were killed and used as intermediary controls (ICX and ISH). Among the other 20 CX and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…3), a marker of bone resorption (Robins 1994). Similar eect of endurance running upon bone metabolism have been previously reported in male rats (Horcajada et al 1997;Horcajada-Molteni et al 1999). Concerning BMD, exercise had no immediate eect on femoral density: total diaphyseal or metaphyseal density was no dierent in IE and IR.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…3), a marker of bone resorption (Robins 1994). Similar eect of endurance running upon bone metabolism have been previously reported in male rats (Horcajada et al 1997;Horcajada-Molteni et al 1999). Concerning BMD, exercise had no immediate eect on femoral density: total diaphyseal or metaphyseal density was no dierent in IE and IR.…”
Section: Discussionsupporting
confidence: 74%
“…In the same way, endurance training, starting only 3 months after orchidectomy, also restores femoral bone density and mineral content in rats (Horcajada-Molteni et al 1999). However, is endurance running, performed during the 3 months before orchidectomy, able to prevent androgenic de®ciency-induced bone loss?…”
Section: Introductionmentioning
confidence: 88%
“…In men, Stepan et al (25) reported an increase in bone turnover and a rapid decrease in lumbar spine BMD in response to orchidectomy. In growing (10,11,28) and aged or mature ORX rats (5,24,27,31,32), previous studies have also been suggested that androgen deficiencyinduced cancellous bone loss is, at least transiently, associated with increased bone formation and resorption. Bone development was inhibited immediately after orchidectomy in growing rats (27,28) but not rapidly in mature rats (4).…”
mentioning
confidence: 98%
“…In our study as well, we discovered that mirtazapine, which is a norepinephrine and specific serotonergic antidepressant, has a negative influence on BMD and reduces the mechanical strength of bones in the femoral neck region. In rodents, physical activity prevents decreases in BMD as it does in humans, which suggests that increased physical activity could be useful in the prevention of bone mineral loss, regardless of gonadal hormone deficiency [16]. Therefore, reduced locomotor activity could be the factor contributing to the significant decrease in BMD in the left and right femurs in the ORX MIRTA group compared with the ORX group.…”
Section: Discussionmentioning
confidence: 99%